The Proof-of-Concept: The Transformation of Naphthalene and Its Derivatives into Decalin and Its Derivatives during Thermochemical Processing of Sewage Sludge - Jacek Łyczko; Jacek A. Koziel; Chumki Banik; Andrzej Białowiec (Energies, 2021)
One solution for sewage sludge (SS) management is thermochemical treatment due to torrefaction and pyrolysis with biochar production. SS biochar may contain toxic volatile organic compounds (VOCs) and polyaromatic hydrocarbons (PAHs). This study aimed to determine the process temperature’s influence on the qualitative PAHs emission from SS-biochar and the transformation of PAHs contained in SS. SS was torrefied/pyrolyzed under temperatures 200–600 °C with 1 h residence time. The headspace solid-phase microextraction (SPME) combined with gas chromatography and mass spectrometry (HS-SPME-GC-MS) analytical procedure of VOCs and PAHs emission was applied. The highest abundance of numerous VOCs was found for torrefaction ranges of temperature. The increase of temperatures to the pyrolytic range decreased the presence of VOCs and PAHs in biochar. The most common VOCs emitted from thermally processed SS were acetone, 2-methylfuran, 2-butanone, 3-metylbutanal, benzene, decalin, and acetic acid. The naphthalene present in SS converted to decalin (and other decalin derivatives), which may lead to SS biochar being considered hazardous material.